Energy for rural and island communities proceedings of the conference, held in Inverness, Scotland, 22-24 September 1980 - Twidell, John (Oxford Pergamon Press, 1981)
Energy for Rural and Island Communities covers the proceedings of the conference held in Inverness, Scotland on September 22-24, 1980, which aims to gather several professionals concerned with energy supplies for island and rural communities in the 1980s. The papers in this collection are divided into six themes. The first three major topics the papers tackle are the strategy and action in providing energy resource to rural and island communities; the community energy use and generation; and the renewable energy supplies. Other papers discuss several energy sources such as wind, water, and solar. The last part is devoted to presenting papers on development and planning in relation to energy consumption of island and rural communities. This compendium will be invaluable to government and private sectors, educational institutions, and others interested in studying the energy resource, consumption, and generation for island and rural populations.--Provided by publisher.
Includes bibliographies and indexes.
Keywords: Power resources -- Congresses; Electronic books